PERAN INTEGRASI BUDAYA DALAM PENDIDIKAN KEPEMIMPINAN: MEMBANGUN KEHARMONISAN DAN STABILITAS SOSIAL DI MASYARAKAT MAJEMUK INDONESIA - Ainil Mardiah; Wina Apriana; Saswitri Indra; Sinta; Regina Okta Audini; Chintia Essa Bella; Alfroki Martha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research examines the role of cultural integration in leadership education to create social harmony and stability in Indonesia's pluralistic society. The issue raised is the extent to which current leadership education is able to accommodate local cultural values. The purpose of this research is to analyse the importance of cultural integration in leadership education and identify effective models. The research method used is a literature study, by tracing literature from relevant journals, books and official documents. The results show that multicultural education plays an important role in creating inclusive, tolerant and adaptive leaders. Factors such as institutional support, community involvement, and cross-cultural training determine the success of cultural integration. The local culture-based leadership education model has proven effective in enhancing social stability and harmony in pluralistic societies.